Efecto de la piridoxina en algunos marcadores de la respuesta inflamatoria, estrés oxidativo y la función renal en el paciente diabético tipo 2 tratado con metformina - Rodríguez Correa, María del Pilar (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
Type 2 diabetes (DM 2) is a global health problem, leading cause of death in women and the second for men. Oxidative stress along with the inflammatory process passive play an important role in the development of late complications of DM, due to the formation of advanced glycation endproducts (AGEs) which promote systemic inflammatory response. Diabetic nephropathy (DN) is the leading microvascular complication. Use of pyridoxine (B6) has a significant anti-inflammatory action and previous studies demonstrate its potential benefit in incipient ND hence the interest in the use thereof as a therapeutic intervention OBJECTIVE: Determine the effect of metformin associated pyridoxine renal function, oxidative stress and inflammatory response in patients with type 2 diabetes. MATERIAL AND METHODS: It is a clinical trial involving 58 patients of 30-70 years old, both sexes diagnosed with type 2 diabetes within 10 years of evolution in treatment with metformin, which were determined glycemic control and markers of metabolic, renal function , inflammatory response and oxidative stress. The study was conducted over a period of 6 months with an intervention group administered with pyridoxine 100mg orally every 24 hours and a control group; performing biochemical determination baseline, 3 and 6 months. In the statistical analysis the data were presented as means ± standard deviation for quantitative variables and percentages and frequencies for qualitative variables. We applied repeated measures ANOVA and T tests for variables with two determinations. Statistical significance was accepted at p <0.05.

La diabetes tipo 2 (DM2) es un problema de salud mundial, primera causa de muerte en mujeres y la segunda en hombres. El estrés oxidativo junto con el proceso inflamatorio pasivo juega un papel importante en el desarrollo de las complicaciones tardías de la DM, debido a la formación de productos finales de glicosilación avanzada (AGEs) que favorecen la respuesta inflamatoria sistémica. La nefropatía diabética (ND) es la principal complicación microvascular. El uso de piridoxina (B6) presenta una importante acción antiinflamatoria y estudios previos demuestran su posible beneficio en la ND incipiente; de ahí́ el interés en el uso de la misma como una terapia de intervención. OBJETIVO: Determinar el efecto de la piridoxina asociada a metformina en la función renal, estrés oxidativo y respuesta inflamatoria en el paciente con diabetes tipo 2. MATERIAL Y METODOS: Es un ensayo clínico que incluyó 58 pacientes de 30 a 70 años de edad, ambos sexos con diagnostico de diabetes tipo 2 con menos de 10 años de evolución en tratamiento con metformina, a los que se determinaron marcadores de control glucémico y metabólico, función renal, respuesta inflamatoria y estrés oxidativo. El estudio se llevó a cabo en un periodo de 6 meses, con un grupo de intervención al que se administró 100mg de piridoxina vía oral cada 24 hrs. y un grupo control; realizando determinación bioquímica basal, 3 y 6 meses. El análisis estadístico se presentó como media ± desviación estándar y porcentaje para variables cuantitativas y en frecuencias para las cualitativas. ANOVA para medidas repetidas y T de student para variables con dos determinaciones. La significancia estadística se aceptó una p <0.05.
Facultad de Ciencias Médicas y Biológicas. Especialidad en Medicina Familiar
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/4214; info:eu-repo/classification/cti/3; FCMB-E-2014-0460; Respuesta inflamatoria; Diabetes tipo 2; Nefropatía